The impact of Babesia ovis-infected Rhipicephalus bursa larvae on the severity of babesiosis in sheep - Ozubek, Sezayi; Ulucesme, Mehmet Can; Ceylan, Onur; Sevinc, Ferda; Aktas, Munir (Frontiers Media Sa, 2025)
Ovine babesiosis, caused by Babesia ovis, is a significant tick-borne disease affecting sheep globally, with severe economic implications for sheep farming, particularly in T & uuml;rkiye. Babesia ovis is transmitted exclusively by adult Rhipicephalus bursa ticks, but the potential role of infected larval stages in modulating disease severity has remained unclear. This study investigated whether infestation with B. ovis-infected R. bursa larvae reduces the severity of babesiosis following subsequent exposure to infected adult ticks. Three experimental sheep were infested with B. ovis-infected larvae, while three control sheep were infested with Babesia-free larvae. Both groups were subsequently exposed to B. ovis-infected adult R. bursa. Daily clinical, molecular, and serological monitoring revealed no clinical signs of babesiosis or B. ovis infection following larval infestation. However, all sheep developed severe clinical babesiosis after exposure to infected adult ticks. No significant differences in disease severity, parasitemia levels, or clinical outcomes were observed between the experimental and control groups, indicating that larval infestation does not confer protection or lead to milder disease courses. These findings confirm the exclusive role of adult R. bursa in B. ovis transmission and emphasize the critical need for vector control strategies targeting adult tick populations during peak activity. This study highlights the importance of understanding stage-specific transmission barriers and their implications for vector-borne disease management. Future research should explore the molecular mechanisms limiting pathogen transmission by immature ticks and investigate comparative transmission dynamics across Babesia species to inform targeted control interventions.
Keywords: Babesia ovis; experimental infestation; ovine babesiosis; Rhipicephalus bursa; transmission dynamics